Design of Web-Based Media Free Sharing and Portfolio for Journalistic Photography - T Tawami; M Irsyad; R Afrendo; D Oktafiani; R U Mega (International Journal of Education, Information Technology, and Others, 2021)
This study aims to design a web-based free media sharing photo and a prototype of a portfolio website for journalistic photography. This study uses a qualitative descriptive observation on three websites that discuss and display the results of photography from several themes. Then the results of these observations are supported by literature studies to achieve results related to photojournalistic web sharing. The results showed the design of web-based media sharing for photojournalism using PHP; Anyone can get good quality photos for news without having to get involved in copyright issues. These results were obtained from the analysis of the website prototype against the PHP interface, Search bar Recommendation, Free images Copyright license, and Portfolio Customization. The conclusion of this research is to create a journalistic photo sharing web. As a form of legal sharing with the official permission of the photo owner to download and share as information. As a means of sharing but it is still in official copyright. The photo sharing web can also organize photo stories as well as become portfolios for photographers.